Complete mitochondrial genome of Cheilio inermis (Labriformes, Labridae) - Ha Yeun Song; Seonmi Jo; Seung-Hyun Jung; Hyun-Ju Hwang; Hye Suck An (Mitochondrial DNA. Part B. Resources, 2018)
In the present report, we describe the first sequencing and assembly of the complete mitochondrial genome of Cheilio inermis. The mitochondrial genome of C. inermis, with 16,494 bp in length, has the typical vertebrate mitochondrial gene arrangement. It contains 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. All the tRNA genes typically formed a cloverleaf secondary structure. Phylogenetic analysis using mitochondrial genomes of 11 species showed that C. inermis formed monophyletic group with other Labridae species.